The Influence of Negative Emotion on Cognitive and Emotional Control Remains Intact in Aging - Zinchenko, Artyom; Obermeier, Christian; Kanske, Philipp; Schröger, Erich; Villringer, Arno; Kotz, Sonja A. (Frontiers in Aging Neuroscience, 2017)
Healthy aging is characterized by a gradual decline in cognitive control and inhibition of interferences, while emotional control is either preserved or facilitated. Emotional control regulates the processing of emotional conflicts such as in irony in speech, and cognitive control resolves conflict between non-affective tendencies. While negative emotion can trigger control processes and speed up resolution of both cognitive and emotional conflicts, we know little about how aging affects the interaction of emotion and control. In two EEG experiments, we compared the influence of negative emotion on cognitive and emotional conflict processing in groups of younger adults (mean age = 25.2 years) and older adults (69.4 years). Participants viewed short video clips and either categorized spoken vowels (cognitive conflict) or their emotional valence (emotional conflict), while the visual facial information was congruent or incongruent. Results show that negative emotion modulates both cognitive and emotional conflict processing in younger and older adults as indicated in reduced response times and/or enhanced event-related potentials (ERP). In emotional conflict processing, we observed a valence-specific N100 ERP component in both age groups. In cognitive conflict processing, we observed an interaction of emotion by congruence in the N100 responses in both age groups, and a main effect of congruence in the P200 and N200. Thus, the influence of emotion on conflict processing remains intact in aging, despite a marked decline in cognitive control. Older adults may prioritize emotional wellbeing and preserve the role of emotion in cognitive and emotional control.